Prognostic value of expression of intracellular and extracellular domains of HER2 in patients with HER2-possitive breast cancer - Dębska, Sylwia; Kusińska, Renata; Czernek, Urszula; Szydłowska-Pazera, Katarzyna; Błasińska-Morawiec, Maria; Dowgier-Witczak, Izabela; Olas, Elżbieta; Kulig, Andrzej; Jakubiak-Wielganowicz, Magdalena; Potemski, Piotr (Contemporary Oncology/Współczesna Onkologia, 2011)
Background : HER2 consists of an extracellular domain (the target for trastuzumab), a transmembrane domain, and an intracellular domain, which is recognized by an antibody used in the immunohistochemical assessment of HER2 overexpression. The study consisted of 31 patients with metastatic breast cancer treated with trastuzumab. The aim of the study was to evaluate retrospectively expression of extracellular and intracellular HER2 domains in primary breast cancers treated with surgery and to assess their correlation with biological features of tumours, disease-free survival, overall survival, as well as progression-free survival and survival since the start of trastuzumab treatment. Material and methods : All these patients relapsed and were treated with trastuzumab because of metastatic disease – none of them received trastuzumab in an adjuvant setting. Two kinds of antibodies were used in immunohistochemical evaluation: against extracellular and intracellular domains of the HER2. Results : A significant correlation between different patterns of HER2 domain overexpression and disease-free survival was found. Disease-free survival (the time from the primary operation to relapse – prior to the start of any palliative treatment) was the shortest in patients with overexpression of both domains compared to patients without overexpression of both domains and the group with intracellular domain overexpression combined with absence of extracellular domain overexpression (median 13.2 vs. 24.3 vs. 52.4 months, p = 0.01). There was no significant difference between these 3 groups of patients in aspects of biological features of tumours, overall survival, progression-free survival and survival since the start of trastuzumab treatment. Conclusion: Concurrent assessment of extracellular and intracellular domains of HER2 may have prognostic value for HER2-positive patients.